Optical Nonlinearity of Thiazine Dyes Doped With Nanoparticles of Liquid Crystals - Ban A. Naser (Journal of Global Pharma Technology, 2018)
The optical nonlinearity of several thiazine dyes such as(azure A and azure B) organic dyes doped with nanoparticles of liquid crystals in ethanol solvent has been studied using diode pump solid state laser at wavelength(457 nm) and power (56 mW) as the source of excitation. The optical responses were characterized by measuring the intensity dependent refractive index (n2) of the medium using the Z-Scan technique. The results indicate that the samples of organic dyes doped with nanoparticles of liquid crystals possess very large linear and nonlinear optical properties as compared with samples of pure organic dyes. This result showed that these organic doped dyes are very suitable for applications in optical devices and can be available for applications as active laser medium.Keywords: Organic laser dyes, Z-Scan technique, Nonlinear optical properties, Liquid crystals.